EFFECT OF SOWING METHOD ON THE GENETIC SIMILARITY OF AN OAT POPULATION SEGREGATING FOR PANICLE WEIGHT - MALONE, Gaspar; MARCHIORO, Volmir Sergio; ZIMMER, Paulo Dejalma; MALONE, Emilia; CARVALHO, Fernando Irajá Felix de; COSTA DE OLIVEIRA, Antonio (Scientia Agraria, 2007)
Increase in selection efficiency, the best knowledge and characterization of the germplasm and maximization of the genetic gains, have been objectives of plant breeders worldwide. New approaches to reach these objectives are constantly implemented by breeding programs. Molecular markers allow the breeder to assess individual genotypes instead of just phenotypes. Selection based in the genotype can be of fundamental importance to understand the function and behavior of Quantitative Trait Loci (QTLs), of difficult phenotypic analysis. This work was carry out with the objective of analyzing the effect of two sowing systems (hill and spaced plant) on the molecular genetic similarity in a segregant population for panicle weight in oat. A total of 23 F3 segregant bulks, driven by two sowing systems, were analyzed with AFLP markers. Genetic similarity and grouping analyses were accomplished using the NTSyS pc 2.1 program. Of the obtained results, based in the molecular genetic similarity, we can infer that the selection pressure exercised in the initial generations was not sufficient to modify the genetic composition of the populations, when driven by hill and spaced plant sowing systems.